Trichobezoar presenting as intestinal obstruction in a child: A case report - G Prabhu, Satish; Murali, Lakshmi; Gayathri, A S (Indian Journal of Case Reports, 2026)
Trichobezoar is a rare cause of gastrointestinal (GI) obstruction resulting from the accumulation of ingested hair. Most affected cases are of young females with underlying psychiatric disorders. It is a slowly progressive condition that later presents with symptoms of GI obstruction. We present the case of a 5-year-old previously healthy girl who presented with progressive abdominal distension, abdominal pain, and vomiting. Ultrasound imaging revealed signs suggestive of intussusception, a common cause of pediatric bowel obstruction. Emergency exploratory laparotomy was done to prevent the risk of delayed intervention and, surprisingly, revealed two boluses of trichobezoar, which were successfully removed. The post-operative period remained uneventful, and psychiatric counseling was initiated. Trichobezoar, though rare, should be considered as a differential diagnosis of terminal ileal obstruction in the pediatric population presenting with acute abdomen, unusual eating habits, and family discord. Various treatment modalities include upper GI endoscopy, laparoscopy, and/or laparotomy depending on the location of obstruction. Most importantly, a comprehensive psychiatric workup has proven beneficial for long-term prognosis.